The effect of laser transformation notching on the controlled fracture of a high carbon (C70S6 ) steel - Zhang, Deen; Harris, S. J.; McCartney, D.G.; Pashby, I.R.; Powell, J.; Shipway, P.H.; Voisey, K.T. (Elsevier, 2008)
A high carbon (C70S6) steel has been laser surface treated using CO2 and Diode lasers in order to produce an embrittled region to act as a fracture notch. Such a process has been investigated as a precursor to the fracture splitting of automotive engine connecting rods. Microstructures of the treated regions have been examined and the fracture behaviour of notched samples has been quantified.